2009
DOI: 10.1136/jme.2008.027052
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing of junior doctors: exploring their experiences, perspectives and accounts: Table 1

Abstract: Junior doctors offered an HIV test under new Department of Health occupational health guidance were disparaging about how the test was offered. The findings of this study affect thousands of junior doctors in the UK, and the impact of these results is extensive. Participants' suggestions regarding how the process of offering an HIV test can be improved are discussed and ethical issues regarding the new Department of Health policy are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Mandatory HIV testing has been introduced for a large number of HCWs in the developed world (Salkeld & McGeehan, 2010 ). Salkeld, McGeehan, Chaudhuri, and Kerslake ( 2009 ) reported that junior doctors who were offered an HIV test as part of their pre-employment occupational health checks by National Health Service Trusts in the United Kingdom were highly critical of the manner the HIV test was offered. In UCH, HCT is prohibited for recruitment and employment purposes (University College Hospital/College of Medicine, 2005 )…”
Section: Discussionmentioning
confidence: 99%
“…Mandatory HIV testing has been introduced for a large number of HCWs in the developed world (Salkeld & McGeehan, 2010 ). Salkeld, McGeehan, Chaudhuri, and Kerslake ( 2009 ) reported that junior doctors who were offered an HIV test as part of their pre-employment occupational health checks by National Health Service Trusts in the United Kingdom were highly critical of the manner the HIV test was offered. In UCH, HCT is prohibited for recruitment and employment purposes (University College Hospital/College of Medicine, 2005 )…”
Section: Discussionmentioning
confidence: 99%
“…Medical and dental students are also required to undergo additional health clearance before being accepted onto their course. The new guidelines have been criticized,143 and it has been argued that in effect mandatory HIV testing has now been introduced for a large number of HCWs 144…”
Section: Hiv-positive Health Care Workersmentioning
confidence: 99%
“…The document recognises that one off testing is no guarantee against future infection, but falls back on the professional codes of practice from regulatory bodies, and the ongoing obligation of healthcare workers to seek professional advice (and testing if necessary), if they have been exposed to a serious communicable disease. The new guidelines have been criticised, 103 and it has been argued that in effect mandatory HIV testing has now been introduced for a large number of health care workers. 104…”
Section: Late Diagnosis and Testingmentioning
confidence: 99%